Potensi Pengembangan Konsep Agro Science and Technology Park (STP) menggunakan Analisis SWOT di Arjasari, Kabupaten Bandung: Potential Development of the Agro Science and Technology Park (STP) Concept using SWOT Analysis in Arjasari, Bandung Regency - Rahmani, Natasha Indah; Sofiantina Rahayu, Kania; Prabandari, Dyah (IPB University, 2023)
Science parks have been emerged and developed in the United States of America to linked the gap between research sectors and industry. For few decades ago, Science and Technology Park (STP) have been developing rapidly in most of countries in Asia. In 1976 Indonesia have established their very first Science and Technology Park. Science and Technology Park in Indonesia became one of government strategy to stimulate innovation based on local resources. Bandung Regency is one of the regions in Indonesia that depend on their agriculture activities. Arjasari Area is one of sub district in Bandung Regency, where most of the area is a rural area that famous from its Clove, Coconut and Coffee plantation. Besides that, Arjasari have many agricultural activities such as Agriculture Wetlands, Dryland farming, Horticultural Agriculture, Clove, Coconut, Coffee Plantation, Production Forest and Middle Industrial Area. Bandung Regency Municipalities have a plan strategy to encourage rural area with tourism. Developing an agriculture science and technology is one of the strategies to boosting an innovation in agricultural sector while promoting the local product of this area. This research is qualitative research using SWOT (Strength, Weakness, Opportunity, Threat) Anlaysis. SWOT Analysis is used to describe the potential innovation and potential problems that may occurs in the future. Bandung Regency nowadays still lack of innovation in agriculture sector. Human Resources skill and competency of Bandung Regency’s local community also still need to be empowering to improve. This lacking of human resources skill needs to be improved widely from many sectors. On the other hand, Bandung regency have a much potential on agricultural sector. ABSTRAK Science Parks atau Taman Sains telah muncul dan dikembangkan di Amerika Serikat untuk menghubungkan kesenjangan antara sektor penelitian dan industri. Science and Technology Park (STP) telah berkembang pesat di sebagian besar negara di Asia. Pada tahun 1976 Indonesia telah mendirikan taman sains dan teknologi pertama mereka. Taman IPTEK di Indonesia menjadi salah satu strategi pemerintah untuk mendorong inovasi berbasis sumber daya lokal. Kabupaten Bandung merupakan salah satu daerah di Indonesia yang menggantungkan hidupnya pada kegiatan pertanian. Kawasan Arjasari merupakan salah satu kecamatan di Kabupaten Bandung yang sebagian besar wilayahnya merupakan kawasan pedesaan yang terkenal dengan perkebunan Cengkeh, Kelapa dan Kopi. Selain itu Arjasari memiliki banyak kegiatan pertanian seperti Pertanian Lahan Basah, Pertanian Lahan Kering, Pertanian Hortikultura, Cengkeh, Kelapa, Perkebunan Kopi, Hutan Produksi dan Kawasan Industri Menengah. Kabupaten Bandung memiliki rencana untuk mendorong kawasan pedesaan melalui pariwisata. Pengembangan ilmu pengetahuan dan teknologi pertanian merupakan salah satu strategi untuk mendorong inovasi di bidang pertanian sekaligus mempromosikan produk lokal daerah ini. Penelitian ini merupakan penelitian kualitatif dengan menggunakan Analisis SWOT (Strength, Weakness, Opportunity, Threat). Analisis SWOT digunakan untuk menggambarkan potensi inovasi dan potensi masalah yang mungkin terjadi di masa depan. Kabupaten Bandung saat ini masih minim inovasi di bidang pertanian. Keterampilan dan kompetensi Sumber Daya Manusia masyarakat Kabupaten Bandung juga masih perlu diberdayakan untuk ditingkatkan. Kurangnya keterampilan sumber daya manusia ini perlu ditingkatkan secara luas dari berbagai sektor. Di sisi lain, Kabupaten Bandung memiliki banyak potensi di sektor pertanian.